Effects of exogenous lactoferrin on characteristics and functions of bovine epididymal, ejaculated and frozen‐thawed sperm. (22nd March 2021) - Kobayashi, Jin; Sasaki, Aya; Watanabe, Asuka; Komine, Kenichi; Kuroishi, Toshinobu; Takada, Naokazu; Sasada, Hiroshi; Sato, Eimei
Abstract: The purpose of this study was to investigate effects of addition of lactoferrin on characteristics and functions of bovine epididymal, ejaculated, and frozen‐thawed sperm. The addition of lactoferrin was significantly ( p  < .05) effective on increasing values of progressive motility, straightness, and linearity in caput epididymal sperm and values of motility in cauda epididymal sperm. When ejaculated sperm were incubated in capacitation medium, percentages of motile and progressively motile sperm decreased largely within the first period of 30 min, followed by only minor changes. However, the addition of lactoferrin significantly lessened the early decreases of these parameters and additionally promoted capacitation‐dependent changes of chlortetracycline staining patterns (from F pattern to B pattern). In other experiments, when ejaculated sperm were exposed to oxidative stress with 100‐µM H2 O2, the addition of lactoferrin partially protected them from dysfunction of flagellar movement and loss of progressive movement. In final experiments with frozen‐thawed samples incubated in the capacitation medium, the addition of lactoferrin effectively survived dying sperm and suppressed occurrence of sperm agglutination. These results may suggest biological and biotechnological potentials of lactoferrin for modulation of bovine sperm viability, motility, capacitation state, and preservation in vitro.